The Impact of Online Learning: Student’s Views - Nopa Yusnilita (ETERNAL (English Teaching Journal), 2020)
This study enlightment how the online learning bring out impact for students achievement. 20 students as participant in this study. The descriptive qualitative was used as method of the study.  Based on the result of questionnare 80% of online learning is interesting for students. 65% of students answer that online learning class are easier that regular class and 5% answer not.  85% of students always prepare their learning with taking notes or record it. 90% of students answer online learning practical for them. When talking about the time of online learning 7% of students feel disturb and hurry but 70% are not. 75% of students ask that online learning is cheaper than they should go to class, because they need to pay for bus fare, lunch, clothes etc. 68% of students always join discussion along the online learning. 75% of students feel more confidence joining online learning that face to face in class. That’s why 60% of students think online learning can improve high quality of learning. And 70% of the teacher always accomodate their students in learning. They teacher also give them feedback after they send their assignment and more of the students feel more confidence with online learning. In summary, online learning provide students practical and flexible way in learning, it also make them more creative and active. Online learning give them some benefit in learning.